‘On-track’ and ‘off-track’ shoulder lesions - Itoi, E. (EFORT Open Rev, 2017)
Shoulder stability depends on the position of the arm as well as activities of the muscles around the shoulder. The capsulo-ligamentous structures are the main stabilisers with the arm at the end-range of movement, whereas negative intra-articular pressure and concavity-compression effect are the main stabilisers with the arm in the mid-range of movement. There are two types of glenoid bone loss: fragment type and erosion type. A bone loss of the humeral head, known as a Hill-Sachs lesion (HSL), is a compression fracture of the humeral head caused by the anterior rim of the glenoid when the humeral head is dislocated anteriorly in front of the glenoid. Four out of five patients with anterior instability have both Hill-Sachs and glenoid bone lesions, which is called a ‘bipolar lesion’. With the arm moving along the posterior end-range of movement, or with the arm in various degrees of abduction, maximum external rotation and maximum horizontal extension, the glenoid moves along the posterior articular margin of the humeral head. This contact zone of the glenoid with the humeral head is called the ‘glenoid track’. A HSL, which stays on the glenoid track (on-track lesion), cannot engage with the glenoid and cannot cause dislocation. On the other hand, a HSL, which is out of the glenoid track (off-track lesion), has a risk of engagement and dislocation. Clinical validation studies show that the ‘on-track/off-track’ concept is able to predict reliably the risk of a HSL being engaged with the glenoid. For off-track lesions, either remplissage or Latarjet procedure is indicated, depending upon the glenoid defect size and the risk of recurrence. Cite this article: EFORT Open Rev 2017;2:343-351.